(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The right to a clean environment is essential and closely connected to the proper to health and well-being. It’s of fundamental importance to note that there is a strong connection between the quality of the environment and thus the health of the people living andor exposed to the environment. Quality life is possible only in an exceedingly superb environment with clean air to breathe, safe water to drink and noiseless atmosphere. Environmental pollution is one all told the foremost severe problems that this living beings face today. Many people haven’t got access to wash air and water and knowledge health problems thanks to the ever increasing pollution. Pollution is that the method of making land, water, air or other parts of the environment dirty and not safe or suitable to use. This might be done through the introduction of a contaminant into a natural environment, but the contaminant doesn’t must be tangible. Read on to hunt out out more about specific types of pollution. Keeping of these seeable attempt has been made to assess the effect of pollution on environment. Study has been applied through intensive field work by analysing various literature and available material and eventually their effect on human health has been assessed.